Políticas de ciência, tecnologia e inovaç\~ao no Brasil: Uma análise com base nos indicadores agregados - Luiz Ricardo Cavalcante (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– The aim of this work is to discuss the evolution of the science, technology, and innovation (ST&I) policies in Brazil using the aggregate indicators of research and development (R&D) expenditures and of scientific and technological production. The literature review supports the proposition that the proposed ST&I policies have been gradually overcoming the linear model and incorporating a more systemic view of the innovation process. After a brief review of the path followed by the ST&I policies in Brazil since the 1950s, it is argued that the local policies have been similarly recognizing the systemic nature of the innovation process. However, based upon an analysis of the evolution of the national R&D expenditures, it is argued that the adopted policies still focus on the scientific research. It is also shown that, in spite of the increasing share of Brazil in the world patents granted by the United States Patent and Trademark Office (USPTO), the accelerated growth of the share of Brazil in the world scientific papers indexed by the Institute for Scientific Information (ISI) has been leading to a decreasing relationship between these two indicators. The persistence of policies that focus on scientific instead of technologic and innovative actions is associated to the mismatch between the analytical categories used to support policies formulations and the performing of actions based upon less instrumental concepts.
Keywords: O30; O32; O38; 330; Forschungs- und Technologiepolitik; Innovationspolitik; Brasilien